Dasar Pertahanan Negara: analisa ke atas Angkatan Tentera Malaysia (ATM) dalam konsep pertahanan menyeluruh (HANRUH) - Muhamad Ridzuan, Hashim (2021)
The development of the National Defence Policy (NDP) of Malaysia has been developed since 1957 which also involves the development of service branches of the Malaysian Armed Forces (MAF) namely the Army, Royal Malaysian Navy and Royal Malaysian Air Force. The development of the NDP also involves the implementation of the Total Defense Concept (HANRUH) which places the MAF as the first line of defense in defending national security and defense and assisted by volunteer forces as the second line and other agencies as well as the public as the third line of HANRUH. However, the implementation of HANRUH raises questions about the capabilities of the MAF at this time which is plagued with various problems. Thus, this study examines the problems and challenges faced by MAFs in the concept of HANRUH. This study has the objective to identify the implementation of HANRUH in Malaysia, analyze the problems faced by the MAF and the impact on national security and defense. This study uses qualitative methods to conduct research especially related to aspects of defense and security. This study found that the implementation of HANRUH in Malaysia began in 1970 with the implementation of Security dan Development (KESBAN) and developed as HANRUH in 1986 which placed the MAF as the first line of defense. This study found that the capabilities of MAFs are facing problems such as, poor NDP posture policy, vague defense concept, logistical aspects of MAF services that are problematic, obsolete and old. Even the MAF logistics of all service branches were involved in various accidents. The case of the invasion of the Military Camp in Gerik Perak in July 2000 by some militants, the terrorist invasion of Lahad Datu, Sabah in February 2013, the murdered of the son of a former North Korean President; Kim Jong Nam at Kuala Lumpur International Airport (KLIA) and various maritime intrusion cases show that MAF failure. It indirectly indicates the failure of the implementation of HANRUH practiced by the government.